Reflections on professional learning: Choices, context and culture. (September 2015) - Van Schalkwyk, Susan; Leibowitz, Brenda; Herman, Nicoline; Farmer, Jean
Highlights: The context in which professional learning for the teaching role occurs is complex. Professional learning for teaching requires spaces where academics can flourish. Choices for professional learning are influenced by intrinsic and extrinsic factors. Tensions exist between stated institutional values and teachers' lived experience. Abstract: Understanding factors that enable and constrain the professional learning of academics for their teaching role provides insight into the complex space within which this teaching resides. The work of social realist Margaret Archer informed an analysis of multiple data sources as part of an exercise towards critical reflection and introspection about professional learning at the university. The data confirms previous work, but also takes the conversation forward. The university teacher – seen to be making choices, within a particular context and informed by her perceptions of the prevailing culture and her personal priorities – is central to this discussion. Academic development practitioners should consider how they might influence dominant discourses, and enhance the dispositions of teaching academics to support quality teaching.